Th2 to Th1 Transition Is Required for Induction of Skin Lesions in an Inducible and Recurrent Murine Model of Cutaneous Lupus–Like Inflammation - Haddadi, Nazgol-Sadat; Mande, Purvi; Brodeur, Tia Y.; Hao, Kaiyuan; Ryan, Grace E.; Moses, Stephanie; Subramanian, Sharon; Picari, Xhuliana; Afshari, Khashayar; Marshak-Rothstein, Ann; Richmond, Jillian M. (Frontiers in Immunology, 2022)
Cutaneous lupus erythematosus (CLE) is an autoimmune skin disease characterized by a strong IFN signature, normally associated with type I IFNs. However, increasing evidence points to an additional role for IFNγ, or at least a pathogenic T effector subset dependent on IFNγ, for disease progression. Nevertheless, Th2 effector subsets have also been implicated in CLE. We have now assessed the role of specific T cell subsets in the initiation and persistence of skin disease using a T cell-inducible murine model of CLE dependent on KJ1-26 T cell recognition of an ovalbumin fusion protein. We found that only Th2-skewed cells, and not Th1-skewed cells, induced the development of skin lesions. However, we provide strong evidence that the Th2 disease-initiating cells convert to a more Th1-like functional phenotype in vivo by the time the skin lesions are apparent. This phenotype is maintained and potentiates over time, as T cells isolated from the skin, following a second induction of self-antigen, expressed more IFN-γ than T cells isolated at the time initial response. Transcriptional analysis identified additional changes in the KJ1-26 T cells at four weeks post injection, with higher expression levels of interferon stimulated genes (ISGs) including CXCL9, IRF5, IFIH1, and MX1. Further, injection of IFN-γ-/- T cells fails to induce skin disease in mice. We concluded that Th2 cells trigger skin lesion formation in CLE, and these cells switch to a Th1-like phenotype in the context of a TLR7-driven immune environment that is stable within the T cell memory compartment.